(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Foreign acquisitions have rapidly and effectively transformed India's digital economy, impacting corporate strategies and trajectories beyond immediately observable ownership transformations. This study utilized a qualitative, exploratory comparative case study of two successful Indian digital firms, Flipkart (acquired by Walmart) and MX Player (acquired by Times Internet), to explore foreign ownership impacts on post-acquisition strategic orientation. A recompiling and reviewing of secondary data including industry reports, regulatory filings, news articles, and literature was used to analyze and identify three prominent trends: (1) strategic orientation towards domestic market consolidation, (2) resources diverted away from strategic initiatives either regarding statutory requirements or management task constraints, and (3) capability reduction created by talent loss and cultural integration issues. The study findings indicated that foreign acquisitions tended to limit global aspirations rather than leverage opportunities that supported them—especially in industries with high-localization costs and highly regulated environments. Implications for international business and emerging markets literature will reflect the strategies revealed in the findings specifically, hybrid structures, asset-light partnerships, and policy-enabled globalization as practical frameworks to enable acquired firms to pursue sustainable international growth and reduce exposure to integration challenges. This paper explores the causes, challenges of foreign ownership, and alternative pathways for global growth based on evidences.